388 TREATMENT OF ANASTOMOTIC LEAKAGE AFTER ESOPHAGECTOMY (TENTACLE—ESOPHAGUS) STUDY: FACTORS ASSOCIATED WITH ANASTOMOTIC LEAKAGE SEVERITY. (14th September 2020) - Ubels, S; Verstegen, M; Bouwense, S; Hannink, G; Siersema, P; Klarenbeek, B; van Workum, F; Rosman, C
Abstract: : Anastomotic leakage is a common and severe complication after esophagectomy. It is largely unknown which characteristics contribute to leakage severity. We aimed to investigate which factors are associated with leakage severity and to create an anastomotic leakage severity classification. Methods: The TENTACLE—Esophagus is a multinational retrospective cohort study in which patients with anastomotic leakage after esophagectomy in the period 2011–2019 were included. Detailed data regarding casemix (e.g. age, sex, physical condition, comorbidity, tumor characteristics), surgical procedure (e.g. McKeown, Ivor Lewis, Orringer, anastomotic technique, omental wrap, pleural flap), leakage characteristics (e.g. contamination, drainage at leakage diagnosis, leak circumference) and treatment were collected. The primary outcome is 90-day mortality. Regression analysis will be used to analyze which leakage characteristics are associated with 90-day mortality and to compose an evidence-based anastomotic leakage severity score. The study protocol is accessible at www.tentaclestudy.com . Results: Detailed data of 1407 patients with anastomotic leakage from 70 centers in 20 countries were collected. Anastomotic leakage occurred 0–43 days after surgery and 90-day mortality rate was 11.1%. The TENTACLE—Esophagus study data is currently being validated and it is awaiting full analysis. The results and the evidence based anastomotic leakage severity classification system will be ready for presentation at the ISDE meeting. Conclusion: This is the largest study that investigates which factors contribute to anastomotic leakage severity after esophagectomy. The evidence-based anastomotic leakage severity classification system can be used by clinicians to grade severity of a given leak and might aid clinicians in choosing the most appropriate treatment.